2007
DOI: 10.1089/oli.2007.0021
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide Pyrophosphatase/Phosphodiesterase 1 Is Responsible for Degradation of Antisense Phosphorothioate Oligonucleotides

Abstract: The rapid degradation of unmodified phosphodiester oligodeoxynucleotides (PO-oligos) by exo -and endonucleases limits their application as antisense constructs and requires the synthesis and use of modified oligonucleotides. Phosphorothioate analogs of oligonucleotides (PS-oligos) are much more stable against nucleolytic degradation than their unmodified counterparts, and this is one of the reasons for which they are a promising class of antisense oligonucleotides. However, PS-oligos also undergo slow hydrolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 37 publications
(68 reference statements)
0
26
0
Order By: Relevance
“…11). NPP1 has been reported to even degrade antisense phosphorothionate oligonucleotides, resulting in the formation of a ladder of shorter products and the release of the mononucleoside 5′-phosphorothionate [368].…”
Section: General Properties and Functional Rolementioning
confidence: 99%
“…11). NPP1 has been reported to even degrade antisense phosphorothionate oligonucleotides, resulting in the formation of a ladder of shorter products and the release of the mononucleoside 5′-phosphorothionate [368].…”
Section: General Properties and Functional Rolementioning
confidence: 99%
“…Synthetic PS-oligos have been developed as antisense probes for genomic research and medicinal applications (1,2). These oligonucleotides are promising therapeutic molecules because they are much more stable against nucleolytic degradation in blood and various cellular systems than their natural, unmodified counterparts (3)(4)(5). Their hydrolysis in plasma, kidney, and liver proceeds mainly from the 3Ј end, resulting in the appearance of the mononucleoside 5Ј-phosphorothioates identified in urine from PS-oligo-injected animals (6,7).…”
mentioning
confidence: 99%
“…It is now accepted that the human plasma 3 0 -exonuclease possesses the [R P ]-selective nature and its digestion mechanism proceeds with retention of configuration at a phosphorus atom, that is, the reaction occurs via a two-step mechanism with participation of a covalent enzymesubstrate intermediate (Gijsbers et al 2001;Koziolkiewicz et al 2002). This fact, combined with the result obtained from immunoprecipitation assay with mouse monoclonal antibodies 3E8 binding the native form of NPP1 (also known as plasma cell membrane glycoprotein PC-1, EC 3.1.4.1/3.6.1.9) confirmed that the human plasma 3 0 -exonuclease is a soluble form of PC-1 belonging to the nucleotide pyrophosphatases/ phosphodiesterases (NPPs) family (Wojcik et al 2007), widely distributed and phylogenetically conserved membrane-associated or secreted proteins involved in regulation of various physiological processes, including bone mineralization, calcification of ligaments and joint capsules, signaling by nucleotides and insulin, and the differentiation and motility of cells (Bollen et al 2000;Goding et al 2003;Stefan et al 2005). Multiple roles of NPPs are consequence, at least in part, of their action on distinct substrates like nucleotides and nucleotide derivatives as well as lysophospholipids and choline phosphate esters.…”
Section: Introductionmentioning
confidence: 52%